PELAKSANAAN PENYIDIKAN TINDAK PIDANA PENYEROBOTAN TANAH DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Parasian Limbong, Reinhard Berman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Land is a basic human interests. It is not a secret anymore because in life, people needthe land to live day-to-day activities. But in contemporary times occur annexation of landcreated deliberately (dolus) by parties who are not responsible. However, the police play animportant role in the criminal act of land grabbing, therefore, required the implementation ofcriminal investigations annexation of land in the area of Pekanbaru City Police Law. Thepurpose of this thesis, namely: first, the implementation of criminal investigations annexationof land in the area of Pekanbaru City Police Law; second, the obstacles in the implementationof criminal investigations annexation of land in the area of Pekanbaru City Police Law; Third,efforts made to overcome the obstacles in the implementation of criminal investigationsannexation of land in the area of Pekanbaru City Police Law.This type of research is classified in this type of sociological juridical research. Becausein this study the authors directly conduct research on the location or point examined in order toprovide a complete and clear picture of the problems examined, the study was conducted inPekanbaru City Police. The data used is primary data, secondary data and data tertiary,technical data collection using interviews and literature study.Based on the results of research and discussion can be concluded that the First, theimplementation of criminal investigations annexation of land in the area of Pekanbaru CityPolice Law does not function as it should; Second, obstacles in the implementation of thecriminal investigation annexation of land in the jurisdiction of City Police Pekanbaru is thepresence of internal factors: the police officers are limited, lack of facilities, lack of expertpolice in handling criminal cases land grabbing and external factors: the difficulty in calling awitness; difficulty in calling the expert testimony; the complainant long did report to the police;Third, efforts made in overcoming obstacles in the implementation of the criminal investigationagainst land invasions are the internal factors, namely the addition of personnel of policeinvestigators from the resort town of Pekanbaru, the addition of patrol cars and vehiclesbelonging to City Police Pekanbaru, updates on the things that are inventory and property forthe execution of police duties, and the effort to external factors coordinate with party landAgency in resolving criminal cases annexation of land as soon as possible, for a witness whohas died police summon the heirs and witnesses are not domiciled in Pekanbaru police to calland came to where live witnesses. Advice, implementation activities Pekanbaru Policeinvestigation further enhanced; the police should be more assertive in dealing with the crime ofland invasions; party Pekanbaru City Police and the National Land Agency Pekanbarucoordinating higher again.Keywords:Investigation-Police-Crime-Landgrabs.